Legal Basis of Tourism Development in Uzbekistan - Rakhimbayev O'tkir Fayzullayevich (Zien Journals, 2023)
In this thesis, the legal basis of the development of the tourism sector in Uzbekistan, the development of the tourism sector with the help of digitization, electronicization and artificial intelligence tools are presented.
Keywords: innovative development; future; perspective; tourism industry